Pengaruh Model Menu Pendampingan terhadap Pertumbuhan dan Perkembangan Anak Usia Stunting di Desa Cinta Raja Kecamatan Langsa Timur Tahun 2020 - Risnati Malinda; Azhar Azhar (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Children are the nation's assets in the future. It can be imagined, how would the condition of Indonesia's human resources be in the future if many Indonesian children are currently suffering from stunting. The incidence of short children or commonly known as stunting is one of the nutritional problems experienced by toddlers in the world today. In 2017 22.2% or around 150.8 million children under five in the world were stunted. The purpose of this study was to analyze the effect of the mentoring menu model on the growth and development of stunting children in Cinta Raja Village, East Langsa District. This type of research used in this research is quasi-experimental research (quasi experiment) with a pretest posttest design non equivalent control group design. In this study the researchers compared the two research groups with the number of respondents 34 children aged 24-60 months. There is a significant effect of menu assistance on the increase in the height of stunting of children under five in Cinta Raja Village, Langsa Timur District, Langsa City. there is a correlation between the increase in height before being given menu assistance (pretest) and after being given menu assistance (post test). It can be concluded that the increase in Height in the stunting and normal under-five group is significant. It is hoped that families who have children under five are able to provide a balanced nutrition family diet as long as the child is in a period of growth and development so as to prevent stunting.